Effect of HBeAg/anti-HBe coexistence on HBeAg seroconversion in treatment-naïve chronic hepatitis B patients with peginterferon-α - Kaimin Song; Huitong Wang; Dawu Zeng; Yunyun Qian; Zhixiang Guo; Huatang Zhang; Yijuan Zheng; Yongjun Zhou; Xueping Yu; Zhijun Su (Therapeutic Advances in Gastroenterology, 2025)
Background: As an uncommon serological pattern, the effect of hepatitis B e antigen/anti-hepatitis B e (HBeAg/anti-HBe) coexistence on peginterferon-α (Peg-IFN-α) therapy in patients with chronic hepatitis B (CHB) remains unknown. Moreover, Peg-IFN-α is clinically limited due to several side effects. It is of significant value to early identify the favored population for Peg-IFN-α therapy in CHB patients. Objectives: This study aimed to analyze the impact of HBeAg/anti-HBe coexistence on the effectiveness of Peg-IFN-α and to construct a nomogram for predicting the occurrence of HBeAg seroconversion in treatment-naïve CHB patients with Peg-IFN-α therapy. Design: Retrospective, case–control study of treatment-naïve CHB patients with Peg-IFN-α at a tertiary care center. Methods: Data from HBeAg-positive treatment-naïve CHB patients were retrospectively analyzed. Clinical characteristics of the HBeAg/anti-HBe coexistence group were compared with those of the anti-HBe-negative group. In addition, univariate and multivariate logistic regression analyses were performed to identify independent risk factors for HBeAg seroconversion. The nomogram for the prediction of HBeAg seroconversion was constructed and evaluated. Results: A total of 140 HBeAg-positive CHB patients were enrolled. Patients with HBeAg/anti-HBe coexistence accounted for 11.4% of HBeAg-positive patients, and their hepatitis B surface antigen (HBsAg) and HBeAg levels were significantly lower than those of anti-HBe negative patients, but the HBeAg seroconversion rate was higher after Peg-IFN-α treatment. As revealed by multivariate logistic analysis, HBeAg/anti-HBe coexistence, baseline HBsAg, baseline HBeAg, and alanine aminotransferase ratio at baseline were independent correlates of HBeAg seroconversion. The nomogram model constructed based on these four independent correlates demonstrated good discrimination (area under the curve = 0.866), calibration, and clinical adaptability. Conclusion: HBeAg/anti-HBe coexistence is associated with a higher HBeAg seroconversion rate, and the nomogram model constructed based on HBeAg/anti-HBe coexistence performs well in predicting HBeAg seroconversion in treatment-naïve CHB patients treated with Peg-IFN-α therapy.